Technology-based therapy-response evaluation of axial motor symptoms under daily drug regimen of patients with Parkinson’s disease - Wu, Zhuang; Hong, Ronghua; Li, Shuangfang; Peng, Kangwen; Lin, Ao; Gao, Yichen; Jin, Yue; Su, Xiaoyun; Zhi, Hongping; Guan, Qiang; Pan, Lizhen; Jin, Lingjing (Frontiers in Aging Neuroscience, 2022)
Background Axial disturbances are the most disabling symptoms of Parkinson’s disease (PD). Kinect-based objective measures could extract motion characteristics with high reliability and validity. Purpose The present research aimed to quantify the therapy–response of axial motor symptoms to daily medication regimen and to explore the correlates of the improvement rate (IR) of axial motor symptoms based on a Kinect camera. Materials and methods We enrolled 44 patients with PD and 21 healthy controls. All 65 participants performed the Movement Disorder Society-Sponsored Revision of the Unified Parkinson’s Disease Rating Scale part III and the Kinect-based kinematic evaluation to assess arising from a chair, gait, posture, and postural stability before and after medication. Spearman’s correlation analysis and multiple linear regression model were performed to explore the relationships between motor feature IR and clinical data. Results All the features arising from a chair (P = 0.001), stride length (P = 0.001), velocity (P < 0.001), the height of foot lift (P < 0.001), and turning time (P = 0.001) improved significantly after a daily drug regimen in patients with PD. In addition, the anterior trunk flexion (lumbar level) exhibited significant improvement (P = 0.004). The IR of the axial motor symptoms score was significantly correlated with the IRs of kinematic features for gait velocity, stride length, foot lift height, and sitting speed (rs = 0.345, P = 0.022; rs = 0.382, P = 0.010; rs = 0.314, P = 0.038; rs = 0.518, P < 0.001, respectively). A multivariable regression analysis showed that the improvement in axial motor symptoms was associated with the IR of gait velocity only (β = 0.593, 95% CI = 0.023–1.164, P = 0.042). Conclusion Axial symptoms were not completely drug-resistant, and some kinematic features can be improved after the daily medication regimen of patients with PD.